Chalcone-containing dual-targeting PD-L1/tubulin small molecules: a novel approach for cancer immunotherapy - Zhou, Yingxing; Ding, Jingwei; An, Shayu; Wang, Lu; He, Xinyi; Du, Jingjing; Su, Zhenhong; Yao, Xiao (Frontiers in Pharmacology, 2026)
ObjectivesThis study aims to identify novel small-molecule inhibitors capable of dual targeting of PD-L1 and tubulin, intending to enhance cancer immunotherapy.MethodsA combination of computer-aided virtual screening, molecular docking, homogeneous time-resolved fluorescence (HTRF) assays, tubulin polymerization inhibition assays, and in vivo antitumor assays was utilized to identify compounds with dual-targeting potential.ResultsCompound PP-1 exhibited moderate inhibitory activity against the PD-1/PD-L1 interaction (IC50 = 81.1 µM) and showed dose-dependent inhibition of tubulin polymerization (IC50 = 70.1 µM). Molecular docking analysis further confirmed that PP-1 can effectively bind to both PD-L1 and tubulin at the molecular level, supporting its bifunctional targeting capability. Importantly, compound PP-1 (50 mg/kg, P.O.) demonstrated significant antitumor efficacy in a melanoma model, achieving a tumor growth inhibition rate of 42% without apparent systemic toxicity.ConclusionPP-1 demonstrates dual-target inhibitory activity against both the PD-1/PD-L1 immune checkpoint and tubulin polymerization, underscoring its potential as a promising lead compound for the development of next-generation dual-functional anticancer agents.